Poultry litter as a sustainable fertilizer for stockpiled tall fescue during winter grazing in middle Tennessee - Nave, Renata L.G.; Barbero, Rondineli P. [UNESP]; Boyer, Chris N.; Mulliniks, John T.; Corbin, Michael D. (Wiley, 2016)
Poultry litter has been used in crop production for many years and is particularly well suited for use as a plant nutrient source because of its high nutrient content compared with other manures. The objective of this research was to compare forage yield, forage nutritive value, beef cattle performance, and economics of stockpiled tall fescue [Schedonorus arundinaceus (Schreb.) Dumort] fertilized with commercial fertilizer or poultry litter. The research was conducted from October 2013 to April 2015 at the Middle Tennessee AgResearch and Education Center of the University of Tennessee, in Spring Hill. The experimental design was completely randomized with two treatments- ammonium nitrate used as commercial fertilizer or poultry litter-replicated three times. For the plant morphological components and forage nutritive value, there were no differences between N sources. However there was a year × N source interaction (P = 0.04) for crude protein (CP) concentration with CP values averaging 9.8% in 2014 and 10.8% in 2015. There were no differences between N sources for average daily gain (ADG), which was 1.19 lb/day in 2014 and 0.95 lb/day in 2015, or for stocking rate, which was 0.65 animal units (AU) per acre in 2014 and 0.49 AU/acre in 2015. In assessing N requirements of stockpiled tall fescue, producers should consider the cost of buying, transporting, and applying poultry litter compared with the cost of commercial fertilizer sources before making a decision to fertilize a particular pasture.